Corporate Social Responsibility Program of PT Pertamina Patra Niaga Aviation Fuel Terminal (AFT) Ngurah Rai: Welfare Distribution for Farmers through Energy Supply Management Technology in Uma Palak Irrigation as Climate Change Mitigation - Centauri, Farkha Alfa; Hermitasari, Erly Yeniska; Seva, Tahsa Ayu; Malaranti, Erika (Global Writing Academica Researching and Publishing, 2024)
Urban farming now serves not only as a support for urban household food security but also embodies the concept of Tri Hita Karana in the Balinese Hindu community. To sustain agriculture in Desa Adat Peguyangan, Kelurahan Peguyangan, Kecamatan Denpasar Utara, Kota Denpasar, Bali, PT Pertamina Patra Niaga Aviation Fuel Terminal Ngurah Rai implements the CSR program Uma Palak Lestari. This research employs a descriptive approach. Data collection techniques include in-depth interviews. Respondents were selected through purposive sampling, encompassing group leaders and members, community leaders, and relevant government officials. The results indicate that the Uma Palak Lestari Program by Pertamina Patra Niaga AFT Ngurah Rai has introduced innovations aimed at addressing urban agriculture challenges in Munduk Palak Subak Sembung, North Denpasar. This program, in collaboration with the Munduk Palak farmers group organized under the Joint Business Group (KUB) Uma Palak Lestari, has developed the Uma Palak Energy Supply Management Irrigation (SIUMA) technology. SIUMA is a hybrid renewable energy technology designed to adapt to climate change. SIUMA serves as a survival guide to help farmers endure drought confitions.